In Situ Synthesis of MOF/Thermoresponsive Hydrogel Composite-Based Adsorbents for Water Treatment - Faezeh Mousavi-Torkamani; Massomeh Ghorbanloo; Mitra Saffari; Nastaran Maddahzadeh (Nanochemistry Research)
The current research seeks to introduce a new catalytic system called poly(N-isopropylacrylamide-co-2-acrylamido-2-methylpropane sulfonic acid sodium)- [Zn2(BDC)1.5(L)(DMF)], which refers to a thermo-responsive amphiphilic Zinc-MOF-paired ionic co-polymeric hydrogel, composed of poly(N-isopropylacrylamide-co-2-acrylamido-2-methylpropane sulfonic acid sodium) hydrogel and [Zn2(BDC)1.5(L)(DMF)] as a metal-organic framework. The catalytic system was constructed using free-radical polymerization at ambient temperature. Dynamic light scattering was then used to assess the temperature-responsiveness of the adsorbent and determine the hydrodynamic radii of the constructed compounds. LCST of the composite was around 56-58 ͌C. To determine the amounts of Zn metals in the prepared compound, atomic absorption spectroscopy (AAS) was used. The prepared composites were used to adsorb Methylene Blue from aqueous solutions. The results showed that p(NIPAM-co-NaAMPS)‐([Zn2(BDC)1.5(L)(DMF)]) composite had the potential to effectively adsorb the methylene blue in the solid-liquid biphasic reaction system. After the catalytic activity was completed, the adsorbent could be easily separated from the reaction media by manipulating temperature.  It could also be reused without any loss in activity.